A thermochromic ionization pressure sensor and its preparation method
By using thermochromic crystallization and anhydrous ethanol to prepare a thermochromic film and introducing ionic liquid into the dielectric layer, the problem of poor combination of ionization sensing and thermochromic performance in the prior art is solved, high-sensitivity pressure sensing and visual temperature response are achieved, and a versatile and environmentally friendly preparation process is provided.
Patent Information
- Application Number
- CN202411896952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the prior art, the functional combination of ionization sensing and thermochromic properties has not been improved. In the preparation method of thermochromic materials, there will be problems such as harmful solvent leakage and solvent residue affecting the mechanical properties of the film, and the preparation process is not green and environmentally friendly.
Thermochromic crystallization and anhydrous ethanol were used as solvents to prepare a thermochromic film through filtration and crystallization processes, and two ionic liquids [EMIM][OTF] and [EMIM][TFSI] were introduced into the dielectric layer to improve the ionic conductivity and thermochromic properties of the film by appropriate proportion settings.
It effectively avoids the problems of harmful solvent leakage and reduced mechanical properties of films, realizes high-sensitivity pressure sensing and visual temperature response, and has a versatile and environmentally friendly preparation process.
Smart Images

Figure CN119349900B_ABST
Abstract
Description
Technical Field
[0001] The invention provides a thermochromic ionization pressure sensor and a preparation method thereof, and relates to the technical field of sensors. Background Art
[0002] With the popularization and development of concepts such as the Internet of Things, big data, and personalized medicine, portable and wearable sensors have become a new trend in the development of sensing technology. Flexible pressure sensors can sense mechanical stimulation like human skin, and are therefore regarded as one of the key technologies for human health monitoring and human-machine interface applications.
[0003] According to the sensing principle, flexible pressure sensors can be roughly divided into four types: capacitive, resistive, triboelectric and piezoelectric. Among them, piezoelectric and triboelectric electronic pressure sensors can only be applied to dynamic loads, while resistive pressure sensors are easily affected by temperature and water. Capacitive sensors are studied in depth because of their simple manufacturing, good anti-interference and excellent long-term stability.
[0004] Traditional capacitive sensors often show low sensitivity under high working pressure, and the capacitance value of traditional parallel plate capacitors is only tens of pico-farads, so the human body capacitance (up to hundreds of pico-farads) and other parasitic noise sources (usually tens of pico-farads) have a great impact on the accuracy and stability of the device. Currently, introducing compressible microstructures in the dielectric layer or electrode layer is one of the effective strategies to improve the performance of capacitive sensors. Since the compressible distance of the device is effectively increased, the capacitance increases rapidly in the low pressure range (~ several kilopascals), thereby improving the sensitivity of the device. However, due to the limited compression range of the microstructure, the sensitivity of traditional capacitive sensors is low, and the resolution is low under high pressure.
[0005] Ionization sensing is a new sensing mechanism developed in recent years. It records the pressure value by measuring the capacitance of the ion-electron double layer (EDL) that changes under pressure. Compared with other sensing mechanisms such as resistance, voltage and capacitance, ionization sensing has extremely high pressure response sensitivity, signal-to-noise ratio, anti-interference, pressure resolution, etc. In addition, it also has unique characteristics such as high transparency and wide dynamic and static force response. This sensing mechanism can effectively resist environmental noise and human body capacitive noise, which greatly helps to improve flexible pressure sensors and wearable applications, and leads product innovation in application fields such as environmental interaction, health monitoring, and motion recognition.
[0006] In addition, thermochromic materials are a type of optical modulation material based on the significantly different thermal radiation properties of the material before and after the phase change temperature. They are special materials that can change color with temperature. They show different colors at different temperatures and have a wide range of application potentials. Giving thermochromic properties to ionization sensors will give them a more intelligent application prospect. In the preparation of existing thermochromic thin film materials, the thermochromic solution is generally mixed with the raw materials and dried to prepare a film. However, this process may introduce non-volatile solvents, resulting in unnecessary solvent residues, affecting the mechanical properties of the material, and there is a risk of leakage of solvents that are harmful to the human body. For example, in a paper titled Stretchable Polydimethylsiloxane Composites with Emulsified Ionic Materials and Thermochromic Applications, a thermochromic material was dissolved in ethylene glycol, and the solution was encapsulated in a PDMS colloid and cured to prepare a thermochromic film. Although the film prepared by this method exhibited stable thermochromism, residual ethylene glycol liquid was eventually found on the cured PDMS film, and a small amount of ethylene glycol liquid leakage still occurred during subsequent use. In addition, due to the presence of ethylene glycol droplets, the tensile stress and tensile strain of the film decreased.
[0007] In the preparation method of ionization sensors, it is a common choice to introduce ionic liquids to realize the ion-electron double layer effect of electrodes and dielectric films. However, it is generally impossible to take into account both high sensitivity and wide working range at the same time. For example, the literature named Supercapacitive Iontronic Nanofabric Sensing introduced ionic liquids [EMIM][TFSI] to prepare supercapacitive ion-electronic nanofabric sensors, providing 114nF kPa −1 The pressure-capacitance sensitivity of the material is improved, but the working range is limited to about 10 kPa. At the same time, ionic liquids are also involved in the preparation of thermochromic materials. The combination of ionic liquids with other thermochromic materials can improve the optical properties of the materials. For example, the paper titled Ionic-Liquid-Based Printable Materials for Thermochromic and Thermoresistive Applications studies the optical properties of thermochromic materials based on PVDF and ionic liquid bis(1-butyl-3-methylimidazole) tetrachloride ([Bmim] 2 [NiCl 4 ]) thermochromic materials, with different contents of [Bmim] in the polymer matrix were developed 2 [NiCl 4] to prepare smart materials with thermochromic and thermal resistance properties.
[0008] However, the introduction of ionic liquids will also cause some problems while achieving thermochromic and ionization sensing performance: for example, the device packaging process of ionic droplets is complex, there is a risk of liquid leakage, the evaporation of droplets will also affect the subsequent stability of the device, and the device response time is long. These defects are not conducive to the realization of wearable devices for the human body. At the same time, there are few reports on the effective combination of thermochromic performance and ionization sensors. In existing academic research, most literature generally involves giving thermochromic performance to traditional capacitive sensors. For example, this paper named Oblique Pyramid Microstructure-Patterned Flexible Sensors for Pressure and Visual Temperature Sensing developed a multifunctional tactile sensor, designed an oblique pyramid microstructure in the dielectric layer of the capacitive sensor, and significantly improved the sensitivity of the sensor compared with the traditional pyramid sensor. At the same time, the visual sensing mechanism based on the inherent thermochromic properties in the dielectric layer design is used to integrate the temperature sensing feature. Although this method integrates thermochromic performance and capacitive sensing technology, the sensitivity of the prepared sensor is within the pressure range of 0-25kPa, and the sensitivity is quantified as S=1.07%kPa. -1 , its sensitivity is far less than that of ionization sensors.
[0009] Based on the above, the existing technology has not yet perfected the functional combination of ionization sensing and thermochromic performance, and the preparation method of thermochromic materials may have problems such as leakage of harmful solvents, residual solvents affecting the mechanical properties of the film, and the preparation process is not green and environmentally friendly. The above defects are what those skilled in the art hope to overcome. Summary of the invention
[0010] The present invention provides a thermochromic ionization pressure sensor and a preparation method thereof, which are used to solve the above problems:
[0011] A thermochromic ionization pressure sensor, the thermochromic ionization pressure sensor comprising an ion film dielectric layer and an electrode layer, the electrode layer comprising a first electrode layer and a second electrode layer, the ion film dielectric layer being arranged between the first electrode layer and the second electrode layer; the first electrode layer comprising a first thermochromic film and a first conductive silver paste, the first conductive silver paste being arranged on the side of the first thermochromic film facing the ion film dielectric layer; the second electrode layer comprising a second thermochromic film and a second conductive silver paste, the second conductive silver paste being arranged on the side of the second thermochromic film facing the ion film dielectric layer, and the first conductive silver paste and the second conductive silver paste being arranged overlapping in a direction perpendicular to the ion film dielectric layer.
[0012] The conductive wire of the electrode is led out with a copper wire with an insulating layer using silver paste, and the sensor as a whole has a central symmetrical structure. The electrode contacts the ionic thin film dielectric layer to form a double-layer capacitor, and the change in the size of the double-layer capacitor responds to the change in the contact area between the electrode and the ionic thin film dielectric layer caused by the change in the size of the pressure applied to the pressure sensor.
[0013] Preferably, the thickness of the thermochromic ionization pressure sensor is between 200 and 500 μm.
[0014] A method for preparing the above-mentioned thermochromic ionization pressure sensor comprises the following steps:
[0015] preparing an ion film dielectric layer, a first electrode layer and a second electrode layer respectively;
[0016] The ionic thin film dielectric layer is placed between the first electrode layer and the second electrode layer, and the first conductive silver paste and the second conductive silver paste are overlapped in a direction perpendicular to the ionic thin film dielectric layer.
[0017] Preferably, the method further includes: connecting the two output-end electrode lines to the first conductive silver paste and the second conductive silver paste in a one-to-one correspondence, and encapsulating the edges of the first electrode layer and the second electrode layer.
[0018] Preferably, the first electrode layer and the second electrode layer are prepared by the following steps: dissolving thermochromic crystals and poly(vinylidene fluoride-co-hexafluoropropylene) powder in a mixed solution of N,N-dimethylformamide and anhydrous ethanol and stirring evenly, preparing a thermochromic film by spin coating and drying; coating an appropriate amount of conductive silver paste on the thermochromic film, and then drying to obtain an electrode layer.
[0019] Preferably, the thermochromic crystals are prepared by the following steps: choline chloride powder, nickel chloride hexahydrate and anhydrous ethanol are fully mixed to obtain a yellow-green suspension, the suspension is filtered, and the obtained liquid is heated and dried to prepare the thermochromic crystals.
[0020] Preferably, the ionic thin film dielectric layer is prepared by the following steps: taking thermochromic crystals and poly (vinylidene fluoride-co-hexafluoropropylene) powder and dissolving them in a mixed solution of N,N-dimethylformamide and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate and 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt and stirring them evenly, and preparing the ionic thin film dielectric layer by spin coating and drying.
[0021] Preferably, in the step of preparing the thermochromic crystal, the mass ratio of choline chloride powder, nickel chloride hexahydrate, and anhydrous ethanol is 5 to 9: 0.463 to 1.063: 12 to 20. More preferably, the mass ratio of choline chloride powder, nickel chloride hexahydrate, and anhydrous ethanol is 7: 0.663: 15.
[0022] Choline chloride is the main component of thermochromic properties. An appropriate amount of choline chloride helps maintain the ionic environment of the liquid, so that the crystal has good thermal responsiveness and reversibility; nickel chloride hexahydrate is the key component of the thermochromic reaction and participates in the thermosensitive color change process. It works together with choline chloride within a suitable range to ensure that the film can reliably change from colorless to blue when heated, and will not affect the light transmittance and flexibility of the film due to excessive. Such parameter settings help to prepare crystals with stable and reversible thermochromic properties, while ensuring the uniformity of the crystalline structure and good thermochromic properties. Anhydrous ethanol is selected as the solvent. On the one hand, considering its volatile characteristics when heated, it will not cause unnecessary liquid residue. On the other hand, compared with other solvents such as ethylene glycol, anhydrous ethanol is more environmentally friendly and non-toxic to the human body. Through this preferred solution, the problem of harmful solvents leaking from the prepared film is effectively avoided.
[0023] In this step, the suspension needs to be filtered. Filtration can remove undissolved particles and impurities that may exist in the suspension to ensure the purity of the solution, which is crucial for the preparation of high-quality thermochromic crystals, because the presence of impurities may affect the uniformity of the crystals and the performance of thermochromic crystals; by removing suspended particles through filtration, the crystal structure formed during the subsequent heating and drying process is ensured to be uniform, which can improve the quality of the crystals and ensure that they can reliably exhibit the expected color change characteristics when the temperature changes.
[0024] Preferably, in the step of preparing the thermochromic crystals, the filtered solution is dried at 80-120° C. for 1-2 hours to prepare the crystals; more preferably, the filtered solution is dried at 100° C. for 2 hours to prepare the crystals.
[0025] This temperature range helps to quickly remove the solvent and promote the formation of crystals: too high a temperature may cause the destruction of the crystal structure or cause instability in the thermochromic properties, while too low a temperature may result in incomplete crystallization or take too long; the drying time is set to 1 to 2 hours to ensure that the solvent can be completely evaporated and crystals can be formed in a stable environment.
[0026] Preferably, in the preparation steps of the first electrode layer and the second electrode layer, the mass ratio of thermochromic crystals, anhydrous ethanol, poly(vinylidene fluoride-co-hexafluoropropylene) and N,N-dimethylformamide is 0.05-0.1:0.3-1:0.2-0.6:3-5; more preferably, the mass ratio of thermochromic crystals, anhydrous ethanol, poly(vinylidene fluoride-co-hexafluoropropylene) and N,N-dimethylformamide is 0.07:0.33:0.3:3; in another preferred embodiment, the mass ratio of thermochromic crystals, anhydrous ethanol, poly(vinylidene fluoride-co-hexafluoropropylene) and N,N-dimethylformamide is 0.1:0.33:0.3:3; in yet another preferred embodiment, the mass ratio of thermochromic crystals, anhydrous ethanol, poly(vinylidene fluoride-co-hexafluoropropylene) and N,N-dimethylformamide is 0.05:0.33:0.3:3.
[0027] The crystal content within this range helps to ensure that the film has good thermochromic properties: this range ensures that the film can show clear color changes when heated, and the crystal content within this range has little effect on the transparency and flexibility of the film; as one of the solvents, the proportion of anhydrous ethanol within this range helps to adjust the viscosity of the solution, making the solution easy to spin-coat to form a uniform film, and the right amount of ethanol also helps to dissolve other components and ensure uniform dispersion; poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) as a matrix material, its proportion has a direct impact on the mechanical properties and flexibility of the film: the right amount of PVDF-HFP can provide sufficient structural strength while maintaining the flexibility of the film, ensuring that it can maintain stable performance under various deformation conditions; N,N-dimethylformamide (DMF) as the main solvent ensures the uniformity and stability of the entire solution. N,N-dimethylformamide (DMF) can effectively dissolve PVDF-HFP and crystals and ensure good film forming properties during spin coating.
[0028] Conductive silver paste has excellent conductivity and can form a low-resistance conductive path on the film, ensuring that the electrode layer can effectively transmit electrical signals, thereby improving the overall performance and response speed of the sensor; after drying, the silver paste will form a stable conductive film. This structure can improve the mechanical stability of the electrode layer, making it less likely to break or peel under external force, ensuring the long-term stable operation of the sensor; the electrode layer is prepared in two steps of coating and drying. This method is simple and easy to use and suitable for large-scale production. The silver paste coating process is flexible and can adapt to the design requirements of different shapes and sizes, simplifying the manufacturing process of the electrode layer.
[0029] Preferably, in the preparation steps of the first electrode layer and the second electrode layer, the thermochromic film is prepared by spin coating at a speed of 30 to 60 rad / min for 30 seconds, and dried at 80 to 120°C for 20 to 40 minutes, and the thickness of the film is 50 to 120 μm; more preferably, the thermochromic film is prepared by spin coating at a speed of 30 rad / min for 30 seconds, and dried at 100°C for 40 minutes, and the thickness of the prepared film is 80 μm.
[0030] The spin coating speed and time within this range ensure that the solution can be evenly distributed on the surface of the substrate, which can prevent the solution from splashing or accumulating, thereby reducing surface defects of the film and forming a film of uniform thickness; at the appropriate drying temperature and time, the solvent is fully evaporated and the film is completely formed, and the film can gradually form a stable structure, avoiding internal stress in the film caused by too fast drying or defects caused by too slow drying.
[0031] Preferably, in the step of preparing the ionic thin film dielectric layer, the mass ratio of thermochromic crystal, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N-dimethylformamide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) is 0.08-0.12:0.4:0.2-0.6:3-5:0-0.3. More preferably, the mass ratio of thermochromic crystal, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N-dimethylformamide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) is 0.09:0.4:0.3:3:0.3; more preferably, the mass ratio of thermochromic crystal, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N-dimethylformamide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide) is 0.09:0.4:0.3:3:0.3; more preferably, the mass ratio of thermochromic crystal, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N -dimethylformamide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt has a mass ratio of 0.09:0.4:0.3:3:0.2; preferably, the mass ratio of thermochromic crystals, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N-dimethylformamide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt is 0.09:0.4:0.3:3:0.1.
[0032] During the preparation process, it was found that adding only a single ionic liquid could not ensure both the thermochromic performance and the electric double layer effect (EDL) of the dielectric film: the sensor prepared by adding only 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM][OTF]) had poor sensitivity, and the sensor prepared by adding only 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][TFSI]) had unsatisfactory thermochromic effect. However, the combined effect of [EMIM][OTF] and [EMIM][TFSI], through the appropriate ratio setting, can effectively improve the ionic conductivity of the film, enhance the capacitance effect, and ensure the thermochromic performance and transparency of the film; uniform film thickness is crucial to the performance of the sensor, because it directly affects the contact area between the electrode and the dielectric layer, and then affects the sensitivity and stability of the sensor. By using these components in appropriate proportions, an ionic film with uniform thickness, good light transmittance and excellent electrical properties can be prepared. The preferred mass ratio setting in step 3 optimizes the ionic conductivity, thermochromic performance and film uniformity by precisely controlling the material ratio, thereby ensuring the high performance of the ionic thin film dielectric layer, making the sensor have higher sensitivity, stability and durability.
[0033] Preferably, in the step of preparing the ionic film dielectric layer, the ionic film is prepared by spin coating at a speed of 30 to 60 rad / min for 30 seconds, and dried at 80 to 120°C for 20 to 40 minutes, and the thickness of the ionic film is 50 to 200 μm; preferably, the ionic film is prepared by spin coating at a speed of 30 rad / min for 30 seconds, and dried at 100°C for 40 minutes, and the thickness of the prepared film is 80 μm.
[0034] The present invention has the following beneficial effects:
[0035] 1. The present invention has significant beneficial effects on the preparation method of thermochromic crystals. By selecting anhydrous ethanol as a solvent and through filtering and crystallization processes, the problems of harmful solvent leakage and reduction of film mechanical properties due to the inability of the solvent to volatilize in the subsequent preparation of thermochromic films are effectively avoided. Ethanol is used as a solvent. On the one hand, its characteristic of being easily volatile when heated will not cause unnecessary liquid residue. On the other hand, compared with other solvents such as ethylene glycol, anhydrous ethanol is more environmentally friendly and non-toxic to the human body.
[0036] 2. The present invention introduces two ionic liquids (1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMIM][OTF] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl imide [EMIM][TFSI]) into the dielectric layer. By setting a suitable ratio, the ionic conductivity of the film can be effectively improved, the interfacial EDL capacitance effect can be enhanced, and the thermochromic performance of the dielectric layer ion film can be ensured, thereby realizing the regulation of ionic liquids on ionization sensing and thermochromic performance.
[0037] 3. The present invention creatively combines thermochromic properties with ionization sensing technology. By rationally combining and packaging the thin film, the sensor avoids the risk of organic solvent leakage and can be directly attached to the skin. It not only has high sensitivity to sense pressure, but also can make a visual response to temperature changes, and has versatility in the practical application of wearable sensing.
[0038] 4. The thermochromic ionization pressure sensor disclosed in the present invention adopts a simple and environmentally friendly process for its preparation method. The process method provided by the present invention is simple to operate, including the electrode layer film material and the dielectric layer are prepared by solution method, which has the advantages of low cost and high scalability. Under the premise of ensuring the wide working range and high sensitivity of the sensor device, its preparation method and process are relatively simple, the production cost is low, and it has broad application prospects in the field of wearable sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic diagram of the sensor structure of the present invention.
[0040] Figure 2 This is a flow chart for the preparation of thermochromic crystals.
[0041] Figure 3 This is a flow chart for the preparation of electrode layer and dielectric layer films.
[0042] Figure 4 The color-changing characteristics of thermochromic films at different temperatures.
[0043] Figure 5 Spectra of thermochromic films at different temperatures.
[0044] Figure 6 This is the stretching curve of the thermochromic film.
[0045] Figure 7 This is the sensitivity diagram of the sensor in Example 1.
[0046] Figure 8a The transient response diagram of loading / unloading an object (100Pa) on the sensor.
[0047] Figure 8bis the response time of loading / unloading an object (100Pa) on the sensor;
[0048] Figure 8c is the recovery time after loading / unloading an object (100Pa) on the sensor;
[0049] Fig. 9 This is the dynamic response diagram of the sensor to various pressures.
[0050] Fig.10 The sensor monitors different breathing states in real time.
[0051] Fig.11 This is a diagram of the sensor detecting the bending state of the finger.
[0052] Fig.12 The following are the response curves of the sensor on the throat when saying "Ni Hao" and "Sensor".
[0053] Fig.13 Graphs showing capacitance-pressure responses of sensors in different embodiments. DETAILED DESCRIPTION
[0054] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0055] like Figure 1 As shown, the thermochromic ionization pressure sensor provided in an embodiment of the present invention includes an ion film dielectric layer 3 and an electrode layer, the electrode layer includes a first electrode layer 1 and a second electrode layer 2, the ion film dielectric layer 3 is arranged between the first electrode layer 1 and the second electrode layer 2; the first electrode layer 1 includes a first thermochromic film 11 and a first conductive silver paste 12, the first conductive silver paste 12 is arranged on the side of the first thermochromic film 11 facing the ion film dielectric layer 3; the second electrode layer 2 includes a second thermochromic film 21 and a second conductive silver paste 22, the second conductive silver paste 22 is arranged on the side of the second thermochromic film 21 facing the ion film dielectric layer 3, and the first conductive silver paste 12 and the second conductive silver paste 22 are overlapped in a direction perpendicular to the ion film dielectric layer 3.
[0056] The embodiment of the present invention also provides a method for preparing the above-mentioned thermochromic ionization pressure sensor, comprising the following steps:
[0057] preparing an ion film dielectric layer, a first electrode layer and a second electrode layer respectively;
[0058] The ionic thin film dielectric layer is placed between the first electrode layer and the second electrode layer, and the first conductive silver paste and the second conductive silver paste are overlapped in a direction perpendicular to the ionic thin film dielectric layer.
[0059] As shown in Figure 2, the thermochromic crystals are prepared by the following steps: choline chloride powder, nickel chloride hexahydrate and anhydrous ethanol are fully mixed to obtain a yellow-green suspension, the suspension is filtered, and the obtained liquid is heated and dried to prepare thermochromic crystals.
[0060] like Figure 3 As shown, the first electrode layer and the second electrode layer are prepared by the following steps: taking thermochromic crystals and poly(vinylidene fluoride-co-hexafluoropropylene) powder and dissolving them in a mixed solution of N,N-dimethylformamide and anhydrous ethanol and stirring them evenly, preparing a thermochromic film by spin coating and drying; coating an appropriate amount of conductive silver paste on the thermochromic film, and then drying to obtain an electrode layer. The ionic film dielectric layer is prepared by the following steps: taking thermochromic crystals and poly(vinylidene fluoride-co-hexafluoropropylene) powder and dissolving them in a mixed solution of N,N-dimethylformamide and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate and 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt and stirring them evenly, preparing an ionic film dielectric layer by spin coating and drying.
[0061] The thermochromic ionization pressure sensor provided by the present invention will be further described below in conjunction with embodiments.
[0062] Example 1
[0063] The detailed preparation process of the thermochromic ionization pressure sensor is as follows:
[0064] Step 1: Preparation of thermochromic crystals
[0065] 7 g of choline chloride powder and 0.663 g of nickel chloride hexahydrate were added to 15 g of anhydrous ethanol, and the mixture was stirred vigorously until the nickel chloride hexahydrate particles were dissolved to obtain a yellow-green suspension; the yellow-green suspension was filtered to obtain a light green solution, and the solution was placed in an oven at 100° C. and dried for 2 hours to prepare crystals. Then the second step was performed.
[0066] Step 2: Preparation of the first and second electrode layers
[0067] Take 0.07g of the prepared crystals and 0.3g of PVDF-HFP powder and dissolve them in a mixed solution of 0.33g of anhydrous ethanol and 3g of DMF. After stirring evenly, drop the solution on a 50mm×50mm glass plate and spin coat it at a speed of 30rad / min for 30s, and dry it at 100℃ for 40min to prepare a thermochromic film with a thickness of about 80μm; use a flexible electronic printer to coat a 10mm×10mm silver electrode area at the center of the thermochromic film and dry it, and use conductive silver paste to lead out the electrical signal and connect it to the copper wire with an insulating layer to prepare the first electrode layer. Use the same method to prepare the second electrode layer. Then perform the third step.
[0068] Step 3: Preparation of ionic thin film dielectric layer
[0069] 0.09g of the prepared crystals and 0.3g of PVDF-HFP powder were dissolved in a mixed solution of 3g of DMF, 0.4g of [EMIM][OTF] and 0.3g of [EMIM][TFSI], and the solution was dropped on a 50mm×50mm glass plate by spin coating at a speed of 30rad / min for 30s, and dried at 100°C for 40min to prepare an ionic thin film with a thickness of about 80μm. Then, the fourth step was performed.
[0070] Step 4: Sensor Assembly
[0071] The silver electrode regions of the first and second electrode layer films are retained and cut into a size of 20 mm × 12 mm. The prepared dielectric layer ion film is cut into a size of 20 mm × 12 mm and placed in the middle of the first and second electrode layer films, and the electrodes in the first and second electrode layers are arranged in a manner that they completely overlap in the vertical direction;
[0072] Scrape off the surface insulation layer at both ends of the copper wire enameled wire, use tape to stick the exposed electrode wire to the silver paste led out from the prepared electrode layer film, thus forming the two output ends of the pressure sensor device, and then encapsulate the edges of the first electrode layer and the second electrode layer with polyimide tape: stick the edges of the placed sensor with tape to complete the sensor assembly. The thickness of the sensor is about 300μm.
[0073] The measurement and test results of the above sensor devices are as follows:
[0074] The solution of the thermochromic film prepared in the second step was spin-coated on a glass substrate and heated at 100°C. The color of the film solution turned blue when heated. The color of the prepared film was sky blue when it was just prepared. When the temperature was lowered to room temperature, the film became transparent. This color change is a reversible process and is related to temperature. Figure 4The color-changing properties of the thermochromic film prepared in the second step at different temperatures are shown. At room temperature, the film is colorless and transparent, and the words "CJLU" can be clearly seen through the film. At 50°C, the color of the film changes from colorless to light blue, and as the temperature rises, the color gradually deepens until the film turns dark blue at 80°C. Figure 5 As shown, the color change of the electrode layer film was quantitatively evaluated by UV-visible spectroscopy in the range of 600-800nm in the temperature range of 30-100℃. When heated from 30℃ to 100℃, the intensity of the blue region increased with increasing temperature, and strong changes were observed in the absorption bands at 656 and 707nm. The two peaks showed similar intensities, independent of temperature, and the peak intensity increased with increasing temperature until 100℃. The observed thermochromic phenomenon was caused by the absorption / dehydration process stimulated by heat. The coordination number of Ni(II) in the film changed from octahedral structure to tetrahedral structure. The process was reversible. When the temperature was reduced to room temperature, the film returned to transparency.
[0075] In order to verify the effect of the crystallization in step 1 on the mechanical properties of the thermochromic film, a control group was set in this embodiment: in step 1, the same mass of ethylene glycol was used instead of anhydrous ethanol. Since ethylene glycol is not easy to volatilize and difficult to prepare crystals, a mixed solution of choline chloride, nickel chloride hexahydrate, and ethylene glycol was used instead of crystallization to prepare the thermochromic film and dielectric layer film in the subsequent steps; in step 1, the filtration and heating crystallization processes were removed from control group 2, and a mixed solution of choline chloride, nickel chloride hexahydrate, and ethanol was used instead of crystallization to prepare the thermochromic film and dielectric layer film in the subsequent steps. Uniaxial tensile tests were performed on the three groups of thermochromic films.
[0076] The stress-strain curves of the thermochromic films of Example 1 and Control Groups 1 and 2 are shown in Figure 6 As shown, the maximum tensile strain of the thermochromic film prepared in Example 1 is about 144%, which is 1.9 times and 2.63 times that of the control group 1 (75.7%) and the control group 2 (54.7%), respectively; in addition, the maximum tensile stress of the film in Example 1 reaches 6.72MPa, which is 1.86 times and 1.25 times that of the control group 1 (3.61MPa) and the control group 2 (5.36MPa), respectively. The thermochromic film prepared by this method has significantly improved tensile properties. It is speculated that this is because the complete evaporation of ethanol avoids the negative impact of solvent residue on the mechanical properties of the film, and the problem of uneven distribution of suspended particles is effectively avoided through filtration and crystallization processes, thereby further improving the overall mechanical properties of the film.
[0077] The sensitivity analysis of the sensor prepared in this embodiment shows that the sensor has different dynamic responses in different pressure ranges. The working range and sensitivity of the sensor are shown in FIG. Figure 7The sensitivity of the sensor changes in different pressure ranges, and the sensitivity S value is calculated. The S value is the slope of the curve in the figure, that is, S value = change in capacitance change rate / change in pressure, capacitance change rate = capacitance change ΔC / initial capacitance C 0 .like Figure 7 As shown, specifically S 1 =17.66KPa -1 (0-1.15KPa), S 2 =6.6KPa -1 (1.15-11KPa), S 3 =11.3KPa -1 (11-72KPa), S 4 =3.88KPa -1 (72-200KPa).
[0078] The real-time response of the sensor to human motion depends on the response time of the sensor. Figure 8a The response electrical signal curve in Figure 8b The response time of the sensor when pressing and releasing 100Pa pressure (260ms) was analyzed. Figure 8c The recovery time (160ms) of the sensor when pressing and releasing 100Pa pressure is analyzed, which is suitable for the needs of rapid response to human behavior.
[0079] The thermochromic ionization pressure sensor prepared by the present invention has excellent pressure sensing performance, safety and wearing comfort, and has potential application prospects in monitoring human physiological signals and transmitting information in wearable electronic devices. In order to verify this concept, several demonstration experiments were designed to monitor the human physiological activities of the sensor.
[0080] Fig. 9 The dynamic response of the ionization pressure sensor prepared in this embodiment to various pressures is shown. Under different pressure loadings, the sensor exhibits excellent capacitance changes and has obvious distinctions for different pressures: the output capacitance signal value increases with the increase of loading pressure.
[0081] When the sensor is fixed on a surgical mask, it can detect the tiny pressure generated by breathing. By observing the frequency and amplitude of the relative capacitance change, the different breathing states of normal, fast and deep breathing can be clearly distinguished. Fig.10 The output capacitance signal changes of different breathing states through the ionized pressure sensor are shown. As the breathing frequency increases, the curve will be denser than normal breathing, and the capacitance change will be greater when deep breathing is performed.
[0082] Sensors can also be used to identify various movements of joints, such as Fig.11As shown in the figure, the sensor is attached to the finger joints and bending experiments are carried out at different angles. Fig.11 The α in the figure represents the finger bending amplitude. According to the peak difference of the relative capacitance change curve, the joint movement amplitude can be easily identified, providing digital guidance for athletes' training.
[0083] like Fig.12 As shown in the figure, the pressure sensor is connected to the larynx by tape to monitor the phonation. When the volunteers said different two-syllable words, such as "Ni Hao" and "Sensor", different capacitance waveforms appeared on the response curve. When each word was repeated many times, capacitance waveforms with similar characteristics appeared repeatedly, indicating that the sensor has good repeatability and stability.
[0084] Example 2
[0085] The detailed preparation process of the thermochromic ionization pressure sensor is as follows:
[0086] Step 1: Preparation of thermochromic crystals
[0087] 7 g of choline chloride powder and 0.663 g of nickel chloride hexahydrate were added to 15 g of anhydrous ethanol, and the mixture was stirred vigorously until the nickel chloride hexahydrate particles were dissolved to obtain a yellow-green suspension; the yellow-green suspension was filtered to obtain a light green solution, and the solution was placed in an oven at 100° C. and dried for 2 hours to prepare crystals. Then the second step was performed.
[0088] Step 2: Preparation of the first and second electrode layers
[0089] Take 0.1g of the prepared crystals and 0.3g of PVDF-HFP powder and dissolve them in a mixed solution of 0.33g of anhydrous ethanol and 3g of DMF. After stirring evenly, drop the solution on a 50mm×50mm glass plate and spin coat it at a speed of 30rad / min for 30s, and dry it at 100℃ for 40min to prepare a thermochromic film with a thickness of about 80μm; use a flexible electronic printer to coat a 10mm×10mm silver electrode area at the center of the thermochromic film and dry it, and use conductive silver paste to lead out the electrical signal and connect it to the copper wire with an insulating layer to prepare the first electrode layer. Use the same method to prepare the second electrode layer. Then perform the third step.
[0090] Step 3: Preparation of ionic thin film dielectric layer
[0091] 0.09g of the prepared crystals and 0.3g of PVDF-HFP powder were dissolved in a mixed solution of 3g of DMF, 0.4g of [EMIM][OTF] and 0.2g of [EMIM][TFSI], and the solution was dropped on a 50mm×50mm glass plate by spin coating at a speed of 30rad / min for 30s, and dried at 100°C for 40min to prepare an ionic thin film with a thickness of about 80μm. Then, the fourth step was performed.
[0092] Step 4: Sensor Assembly
[0093] The silver electrode regions of the first and second electrode layer films are retained and cut into a size of 20 mm × 12 mm. The prepared dielectric layer ion film is cut into a size of 20 mm × 12 mm and placed in the middle of the first and second electrode layer films, and the electrodes in the first and second electrode layers are arranged in a manner that they completely overlap in the vertical direction;
[0094] Scrape off the surface insulation layer at both ends of the copper wire enameled wire, use tape to stick the exposed electrode wire to the silver paste led out from the prepared electrode layer film, thus forming the two output ends of the pressure sensor device, and then encapsulate the edges of the first electrode layer and the second electrode layer with polyimide tape: stick the edges of the placed sensor with tape to complete the sensor assembly. The thickness of the sensor is about 300μm.
[0095] Example 3
[0096] The detailed preparation process of the thermochromic ionization pressure sensor is as follows:
[0097] Step 1: Preparation of thermochromic crystals
[0098] 7 g of choline chloride powder and 0.663 g of nickel chloride hexahydrate were added to 15 g of anhydrous ethanol, and the mixture was stirred vigorously until the nickel chloride hexahydrate particles were dissolved to obtain a yellow-green suspension; the yellow-green suspension was filtered to obtain a light green solution, and the solution was placed in an oven at 100° C. and dried for 2 hours to prepare crystals. Then the second step was performed.
[0099] Step 2: Preparation of the first and second electrode layers
[0100] Take 0.05g of the prepared crystals and 0.3g of PVDF-HFP powder and dissolve them in a mixed solution of 0.33g of anhydrous ethanol and 3g of DMF. After stirring evenly, drop the solution on a 50mm×50mm glass plate and spin coat it at a speed of 30rad / min for 30s, and dry it at 100℃ for 40min to prepare a thermochromic film with a thickness of about 80μm; use a flexible electronic printer to coat a 10mm×10mm silver electrode area at the center of the thermochromic film and dry it, and use conductive silver paste to lead out the electrical signal and connect it to the copper wire with an insulating layer to prepare the first electrode layer. Use the same method to prepare the second electrode layer. Then perform the third step.
[0101] Step 3: Preparation of ionic thin film dielectric layer
[0102] 0.09g of the prepared crystals and 0.3g of PVDF-HFP powder were dissolved in a mixed solution of 3g of DMF, 0.4g of [EMIM][OTF] and 0.1g of [EMIM][TFSI], and the solution was dropped on a 50mm×50mm glass plate by spin coating at a speed of 30rad / min for 30s, and dried at 100°C for 40min to prepare an ionic thin film with a thickness of about 80μm. Then, the fourth step was performed.
[0103] Step 4: Sensor Assembly
[0104] The silver electrode regions of the first and second electrode layer films are retained and cut into a size of 20 mm × 12 mm. The prepared dielectric layer ion film is cut into a size of 20 mm × 12 mm and placed in the middle of the first and second electrode layer films, and the electrodes in the first and second electrode layers are arranged in a manner that they completely overlap in the vertical direction;
[0105] Scrape off the surface insulation layer at both ends of the copper wire enameled wire, use tape to stick the exposed electrode wire to the silver paste led out from the prepared electrode layer film, thus forming the two output ends of the pressure sensor device, and then encapsulate the edges of the first electrode layer and the second electrode layer with polyimide tape: stick the edges of the placed sensor with tape to complete the sensor assembly. The thickness of the sensor is about 300μm.
[0106] Dynamic pressure was continuously applied to the pressure sensors prepared in different embodiments using a pressure testing device, and the capacitance change of the sensor was recorded using an impedance analyzer. Fig.13 The following are the dynamic response curves of the sensors prepared in Example 1, Example 2 and Example 3 under different pressures. The results show that as the content of the ionic liquid [EMIM][TFSI] increases, the sensing performance will also increase.
[0107] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a thermochromic ionization pressure sensor, characterized in that: The following steps are involved: Separately preparing an ion film dielectric layer (3), a first electrode layer (1) and a second electrode layer (2); The ionic thin film dielectric layer (3) is placed between the first electrode layer (1) and the second electrode layer (2), and the first conductive silver paste (12) and the second conductive silver paste (22) are arranged to overlap in a direction perpendicular to the ionic thin film dielectric layer (3); Connecting the two output-end electrode wires to the first conductive silver paste (12) and the second conductive silver paste (22) in a one-to-one correspondence, and encapsulating the edges of the first electrode layer (1) and the second electrode layer (2); The first electrode layer (1) and the second electrode layer (2) are prepared by the following steps: dissolving thermochromic crystals and poly(vinylidene fluoride-co-hexafluoropropylene) powder in a mixed solution of N,N-dimethylformamide and anhydrous ethanol and stirring evenly, preparing a thermochromic film by spin coating and drying; coating an appropriate amount of conductive silver paste on the thermochromic film and drying to obtain an electrode layer; The thermochromic crystals are prepared by the following steps: choline chloride powder, nickel chloride hexahydrate and anhydrous ethanol are fully mixed to obtain a yellow-green suspension, the suspension is filtered, and the obtained liquid is heated and dried to prepare the thermochromic crystals.
2. The method according to claim 1, characterized in that The ionic thin film dielectric layer (3) is prepared by the following steps: thermochromic crystals and poly (vinylidene fluoride-co-hexafluoropropylene) powder are dissolved in a mixed solution of N,N-dimethylformamide and 1-ethyl-3-methylimidazole trifluoromethanesulfonate and 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and stirred evenly, and then the ionic thin film dielectric layer (3) is prepared by spin coating and drying.
3. The method according to claim 1, characterized in that In the preparation step of the thermochromic crystal, the mass ratio of choline chloride powder, nickel chloride hexahydrate and anhydrous ethanol is 5-9:0.463-1.063:12-20.
4. The method according to claim 1, characterized in that In the step of preparing the thermochromic crystals, the filtered solution is dried at 80 to 120° C. for 1 to 2 hours to prepare the crystals.
5. The method according to claim 1, characterized in that In the steps of preparing the first electrode layer (1) and the second electrode layer (2), the mass ratio of thermochromic crystals, anhydrous ethanol, poly(vinylidene fluoride-co-hexafluoropropylene) and N,N-dimethylformamide is 0.05-0.1:0.3-1:0.2-0.6:3-5.
6. The method according to claim 1, characterized in that In the preparation step of the first electrode layer (1) and the second electrode layer (2), a thermochromic film is prepared by spin coating at a speed of 30 to 60 rad / min for 30 seconds and drying at 80 to 120° C. for 20 to 40 minutes. The thickness of the film is 50 to 120 μm.
7. The method according to claim 2, characterized in that In the preparation step of the ionic thin film dielectric layer (3), the mass ratio of thermochromic crystal, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, poly(vinylidene fluoride-co-hexafluoropropylene), N,N-dimethylformamide, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt is 0.08-0.12:0.4:0.2-0.6:3-5:0-0.
3.
8. The method according to claim 2, characterized in that In the preparation step of the ionic film dielectric layer (3), the ionic film is prepared by spin coating at a speed of 30 to 60 rad / min for 30 seconds and drying at 80 to 120° C. for 20 to 40 minutes. The thickness of the ionic film is 50 to 200 μm.
Citation Information
Patent Citations
Flexible sensor based on micro-scale latticed dielectric layer and preparation method and application thereof
CN112932466A
Preparation method of double-signal flexible sensor with color electric signals
CN119017747A